Effect of cover crops mixtures on weed suppression capacity in a dry sub-humid environment of Argentina - Malaspina, Micaela; Chantre, Guillermo Rubén; Yanniccari, Marcos (Frontiers in Agronomy, 2024)
Cover crops (CC) are increasingly used worldwide within integrated weed management scenarios. They are usually established between two commercial crops and are not harvested, grazed, or incorporated into the soil, but remain on the surface during their growth cycle. The aim of this work was to determine the performance of different CC mixtures and their effects on weed suppression in the south-central region of Buenos Aires province, Argentina. Field experiments were carried out in 2019 and 2020 at the CEI Barrow (MDA-INTA, Tres Arroyos), where both binary and ternary CC mixtures were evaluated. Binary mixtures consisted of winter cereals (Avena sativa, Secale cereale) and legumes (Vicia villosa, Vicia sativa) while ternary mixtures were obtained by combining binary mixtures with canola (Brassica napus). Weed emergence counting was performed on a 14- day basis to determine weed total density. Vegetation cover of the CC mixtures as well as biomass production from crops and weeds were estimated. The specific composition of the mixtures showed a greater influence on vegetation cover than on biomass production, which would depend mainly on the prevailing environmental conditions. The type of vetch used, the addition of canola and the proportion of cereals in the mixture determined the CC effect on weeds. CC was consistently more effective in suppressing weed biomass than seedling emergence density. However, weed seedling suppression by CC was similar to or even greater than the chemical-based control (p<0.0001). The average biomass of weeds in all CC (pooled data) was highly reduced when compared to the weedy control (12 vs 259 g m-2, p<0.001), and similar responses were obtained when compared to the chemical fallow (8 g m-2). The mixture S. cereal+ V. villosa+ canola stood out for presenting the highest values of productivity and vegetation cover and high weed suppression. These results provide support for the choice of CC mixtures in a dry sub-humid area of Argentina, aimed at maximizing interference with weeds and also demonstrating their benefits in short- and long-term management. Therefore, CC implementation within crop sequences should be considered as a complementary tool contributing to the development of more sustainable management strategies.